2017
DOI: 10.1088/1748-9326/aa7145
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation anomalies caused by antecedent precipitation in most of the world

Abstract: Quantifying environmental controls on vegetation is critical to predict the net effect of climate change on global ecosystems and the subsequent feedback on climate. Following a non-linear Granger causality framework based on a random forest predictive model, we exploit the current wealth of multi-decadal satellite data records to uncover the main drivers of monthly vegetation variability at the global scale. Results indicate that water availability is the most dominant factor driving vegetation globally: abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
113
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
2
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 133 publications
(145 citation statements)
references
References 62 publications
14
113
0
Order By: Relevance
“…As mentioned in Sect. 3.3, our experiments indicated that lags of more than 6 months do not add extra predictive power (not shown), even though the effect of anomalies in water availability on vegetation can extend for several months (Papagiannopoulou et al, 2017).…”
Section: Spatial and Temporal Aspectsmentioning
confidence: 60%
See 4 more Smart Citations
“…As mentioned in Sect. 3.3, our experiments indicated that lags of more than 6 months do not add extra predictive power (not shown), even though the effect of anomalies in water availability on vegetation can extend for several months (Papagiannopoulou et al, 2017).…”
Section: Spatial and Temporal Aspectsmentioning
confidence: 60%
“…In those regions, more that 40 % of the variance of NDVI anomalies can be explained by antecedent climate variability. These results are further investigated by Papagiannopoulou et al (2017), who highlight the crucial role of water supply for the anomalies in vegetation greenness in these and other regions. On the other hand, the variance of NDVI explained in other areas, such as the Eurasian taiga, tropical rainforests, or China, is again below 10 %.…”
Section: Linear Versus Non-linear Granger Causalitymentioning
confidence: 91%
See 3 more Smart Citations